Repeatability of the macular pigment spatial profile: A comparison of objective versus subjective classification. Issue 7 (29th August 2018) - Ctori, Irene; Mahroo, Omar A.; Williams, Katie M.; Hammond, Christopher J.; Huntjens, Byki
Abstract: Purpose: Classification of macular pigment (MP) spatial profile phenotypes varies and is often based on subjective visualisation. We investigated repeatability of MP optical density (MPOD) comparing an objective versus subjective profiling system. Methods: The coefficient of repeatability (CoR) was calculated for point MPOD values (0–3.8°) obtained by dual‐wavelength fundus autofluorescence (FAF) from two scans obtained in a single visit of 40 healthy individuals (39 ± 9 years). For each individual's dataset, the MP profile was classified as exponential, ring‐like or central dip using an objective method (based on deviations away from an exponential fit), as well as by subjective visual profiling. Existing FAF images of 88 monozygotic (MZ) and 69 dizygotic (DZ) twin pairs were reanalysed using the objective profiling method and concordance and heritability of ring‐like profiles determined. Results: The CoR was 0.23 at 0° and 0.06 at 0.8°. Agreement of objective profiling between scans was excellent ( κ  = 0.85, 95% CI 0.69 to 1.00; p < 0.0005). Subjective profiling showed moderate agreement between scans ( κ  = 0.48, 95% CI 0.23 to 0.73; p < 0.0005). Agreement between objective and subjective classification was low ( κ  = 0.23, 95% CI 0.04 to 0.42; p = 0.02). Concordance for the ring‐like profile using objective profiling was 0.74 for MZ compared to 0.36 for DZ twins. Heritability was calculated as 81.5% (95% confidence interval 61.1–93.1%). Conclusion: Compared to visual assessment, objective MP profiling is a more reliable method and should be considered in future observational and interventional studies. In addition, MP profile phenotypes showed high heritability.